Mn-Fe catalyzed microwave combustion-plasma hybrid synthesis of 2D chips-like Mn-Fe boosted TiO2 architecture self-assembled of nano-walled honeycomb-like super-macroporous: Green fuel generation. (15th October 2022) - Bekhradinassab, Ensie; Haghighi, Mohammad; Tavakoli, Akram; Shabani, Maryam
Graphical abstract: Highlights: Fabrication of Mn-Fe boosted TiO2 via microwave combustion-plasma hybrid route. 2D chips-like morphology inclouding nano-walls honeycomb-like super-macroporous. Confirming the catalyzing effect of MnFe dopants in combustion process. Potential effect of microwave and MnFe dopants in the promoting of catalyst properties. Potential effect of plasma treatment in the enhancement of catalyst properties. Effectual efficiency of MnFe(2:2)Ti(PMWC) for biodiesel production. Abstract: The productive 2D chips-like Mn-Fe boosted TiO2 as self-assembled nano-walled honeycomb-like super-macroporous was synthesized via the Mn-Fe catalyzed microwave combustion-plasma hybrid to generate biodiesel. The physicochemical property of Mn-Fe doped TiO2 (Mn = 2at% & Fe = 2at.%) were executed by X-ray diffraction, FESEM, BET-BJH, TEM, and TPD-NH3 analyses. Fe and Mn increased the rutile phase and widened pores. 2D surface analysis of plasma-treated catalyst displayed the chips-like framework constructed of nanosheets comprising super-macropores. Plasma destroyed crumbly walls between pores. Hence more acidic sites were exposed, and the diffusion of large feed molecules within pores was eased. The total pore volume was 0.058 and 0.111 cm 3 /g, and the mean pore diameter was 2.94 and 4.57 nm, based on BET-BJH results. Besides, conversion was 91.9 and 96.1 % and after six runs conversion loss was 2.17 and 0.21 % for MnFe(2:2)TiO2 (MWC) and MnFe(2:2)TiO2 (PMWC), respectively. Conversion loss in MnFe(2:2)TiO2 (MWC) was because of the formation of a composite between undoped Mn and Fe and Ti oxides. The plasma made the bond between the composite components stronger and inhibited the leaching of components, so plasma made leaching slight.